Effects of Weissella cibaria CMU on Halitosis and Calculus, Plaque, and Gingivitis Indices in Beagles. (June 2019) - Do, Kyung-Hyo; Park, Ho-Eun; Kang, Mi-Sun; Kim, Jong-Tae; Yeu, Ji-Eun; Lee, Wan-Kyu
Weissella (W.) cibaria strain Chonnam Medical University (CMU) has shown oral colonizing ability and inhibitory effects on the formation of volatile sulfur compounds (VSCs) in vitro studies. The present study was conducted to analyze the effects of the W. cibaria CMU on canine oral health. Halitosis, calculus, plaque, gingivitis, and intraoral microbiota were assessed in 3 groups: control (maltodextrin), W. cibaria CMU low concentration (CMU-L, 2 × 10 7 colony forming unit [CFU]), and high-concentration (CMU-H, 2 × 10 9 CFU). Halitosis was analyzed using both organoleptic evaluation and measurement of VSCs. Intraoral microbiota were analyzed by real-time polymerase chain reaction. From week 4, the total VSC level in the CMU-H group (4.0 ± 1.30 ng/10 mL) was significantly lower than in the control group (6.3 ± 2.28 ng/10 mL). Significant reduction in methyl mercaptan in the CMU-treated groups was also observed. In addition, the plaque index in the CMU-treated groups was significantly decreased. The CMU-treated groups showed significant decreases in Fusobacterium nucleatum, Porphyromonas gingivalis, Prevotella intermedia, and Tannerella forsythia and demonstrated the colonizing ability of W. cibaria CMU in the oral cavity. We demonstrated that W. cibaria CMU suppresses halitosis, colonizes the oral cavity, and inhibits the proliferation of malodor-causing oral bacteria in beagles. According to these results, we expect that W. cibaria CMU could be a new oral hygiene solution by reducing VSC production and inhibiting the growth of oral harmful bacteria in companion animals.